Hubungan Antara Tingkat Kedisiplinan Penggunaan Apd Dengan Tingkat Risiko Gangguan Kesehatan Pada Karyawan Terpapar Iklim Kerja Panas Di Bagian Workshop Pt. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar - Abdullah, Taufiq (2016)
The risk of health problems in employees exposed to the hot working climate is a danger that impact on employee health conditions caused by exposure to hot working climate. In carrying out the production process, the workers at the workshop PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar can not be separated from a variety of physical and chemical exposures. The purpose of this study was to determine the relationship between the level of discipline the use of PPE with the level of risk of health problems in exposed employees are encouraged climate of hot work . This study was an observational study with cross sectional approach. Sampling using sampling with a total population of 30 respondents. Spearman rho statistical tests used in this study showed significant results (p 0.006 <0.05), which means there is a relationship between the level of discipline the use of PPE with the level of risk of health problems in employees exposed to the hot working climate at the workshop PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar.